Theory versus Practice in Planning Education: The View from South Africa. (4th July 2022) - Denoon-Stevens, S. P.; Andres, L.; Jones, P.; Melgaço, L.; Massey, R.; Nel, V.
ABSTRACT: This paper reflects on the ongoing debate between theory and practice in planning, using the example of South Africa. Based on survey responses, it discusses how planning education in South Africa is perceived to prepare students for practice. While we acknowledge that the majority of respondents view their planning education positively, the results reveal challenges regarding the practical application of theory, especially in the case of land-use management. We then respond to calls for contextualised practices of knowing, emphasising the 'local' in planning education so that theory and practice can be combined across contexts.